Prospects after the Voting Reform of the Lisbon Treaty - László Á. Kóczy (Hungarian Academy of Sciences, Institute of Economics, 2010)
The European Union used to make decisions by unanimity or near unanimity. After a series of extensions, with 27 member states the present decision making mechanisms have become very slow and assigned power to the members in an arbitrary way. The new decision rules accepted as part of the Lisbon Treaty did not only make decision making far easier, but streamlined the process by removing the most controversial element: the voting weights. The new system relies entirely on population data. We look at the immediate impact of the reform as well as the long term effects of the dfferent demographic trends in the 27 member states. We find that the Lisbon rules benefit the largest member states, while medium sized countries, especially Central Eastern European countries suffer the biggest losses.
Keywords: C71; D72; 330; European Union; Council of Ministers; qualified majority voting; Banzhaf index; Shapley-Shubik index; a priori voting power; demographics; Abstimmung; Reform; Abstimmungsregel; EU-Staaten